An Analysis upon Synthesis of Novel Resins for Improve Water Quality and Treatment of Yamuna River: Investigating the Efficiency of Novel Resins for Water Quality Improvement (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Water is one of the prime elements responsible for life on the earth. India’s surface water flows through 14 major river basins beyond innumerable medium/minor basins. The climate change is affecting the precipitation and ultimately affects the quantity of freshwater available, whereas, increasing waste water loads from point and non-point sources are deteriorating the quality of surface wateras well as ground water resources. The surface water quality is a very important and sensitive issue and is a great environmental concern worldwide. Surface water pollution by chemical, physical, microbial and biological contaminants can be considered as an epidemic all over the world.Water quality is a significant criterion in matching water demand and supply. Ample degree of freshwater is eminent for biological needs are a vital side of integrated environmental management and sustainable development. The quality of water indices estimation endeavor single value which decrease the big quantity of parameters and represent data in a simple way.The resin was found to be stable in acidic as well as in basic medium. Physicochemical properties of the resin were examined. The total caution exchange capacity was measured and effect of pH and metal ion concentration on ion exchange capacity were studied. The distribution coefficients at different pH were also studied using batch equilibration method.